Measuring the Effect of Islamic Service Quality, Customer Relationship Management, Customer Satisfaction, and Loyalty in Indonesian Islamic Banking - Anjelisa, Anjelisa; Fatmawati, Indah; Nuryakin, Nuryakin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Developing loyal consumers is the foundation for services to sustain a competitive edge, particularly in the banking industry. The purpose of this research is to examine the impact of Sharia-compliant service quality and customer relationship management on customer satisfaction and loyalty. Researchers have also looked into how customer satisfaction mediation might increase customer loyalty. The study employs a quantitative methodology and a survey method. Respondents are priority customers of Indonesian Islamic banks. The sample size was 252 people, who were selected using purposive sampling techniques. Structured equation modeling (SEM) with AMOS as an analysis tool is used in data analysis procedures. According to the findings of this study, the quality of Islamic services and customer relationship management has a positive impact on customer happiness and loyalty. According to the study, customer satisfaction is vital in mediating the relationship between Islamic service quality, customer relationship management, and customer loyalty. These findings highlight the significance of measuring Islamic service quality and customer relationship management in the context of Islamic banks. If the compliance dimension is used thoroughly in the operation of Islamic banking businesses, Islamic banking may gain a competitive advantage over traditional banking.